Ability of Essential Oil Vapours to Reduce Numbers of Culturable Aerosolised Coronavirus, Bacteria and Fungi - Parthasarathi Kalaiselvan; Muhammad Yasir; Rajesh Kuppusamy; Mark Willcox; Ajay Kumar Vijay (MDPI AG, 2022)
Transmission of pathogens present in the indoor air can occur through aerosols. This study evaluated the efficacy of an evaporated mix of essential oils to reduce the numbers of culturable aerosolized coronavirus, bacterium and fungus. The essential oil-containing gel was allowed to vaporize inside a glass chamber for 10 or 20 min. Aerosols of a surrogate of SARS-CoV-2, murine hepatitis coronavirus MHV-1, Escherichia coli or Aspergillus flavus spores were produced using a collision nebuliser and passed through the essential oil vapours, then collected on a six-stage Andersen sampler. The six-stages of the impact sampler capture aerosols in sizes ranging from 7 to 0.65 µm. The number of culturable microbes present in the aerosols collected in the different stages were enumerated and compared to the number of culturable microbes in control microbial aerosols that were not exposed to the evaporated essential oils. After 10 and 20 min evaporation, the essential oils reduced the numbers of culturable aerosolized coronavirus by 48% (log10 reduction = 0.3; p = 0.002 vs. control) and 53% (log10 reduction = 0.3; p = 0.001 vs. control), respectively. The essential oils vaporised for 10 min, reduced the number of viable E. coli by 51% (log10 reduction = 0.3; p = 0.032 vs. control). The Aspergillus flavus spores were mostly observed in the larger aerosols (7.00 µm to 2.10 µm) and the essential oils vaporised for 10 min reduced the number of viable spores by 72% (log10 reduction = 0.6; p = 0.008 vs. control). The vapours produced by a gel containing naturally occurring essential oils were able to significantly reduce the viable numbers of aerosolized coronavirus, bacteria and fungal spores. The antimicrobial gel containing the essential oils may be able to reduce aerosol transmission of microbes when used in domestic and workplace settings.